1992
DOI: 10.1007/bf00833910
|View full text |Cite
|
Sign up to set email alerts
|

Untreated neuroborreliosis: Bannwarth's syndrome evolving into acute schizophrenia-like psychosis

Abstract: In general, meningopolyradiculitis (Bannwarth's syndrome, stage 2 of neuroborreliosis) follows a predictable monophasic self-limiting course. In contrast, we report the case of a patient with an untreated meningopolyradiculitis which evolved into acute schizophrenia-like psychosis due to persistent infection with Borrelia burgdorferi. The psychosis resolved within 1 week of treatment with ceftriaxone. This case shows that the usually benign monophasic meningopolyradiculitis may progress to severe CNS complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 13 publications
0
23
0
Order By: Relevance
“…However, there are some case studies of Lyme disease reporting neurological and psychiatric fi ndings clinically similar to symptoms of schizophrenia in patients with neuroborreliosis (Barnett 1991;Roelcke et al 1992;van den Bergen 1993;Grzywa et al 2004;B ä r et al 2005).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…However, there are some case studies of Lyme disease reporting neurological and psychiatric fi ndings clinically similar to symptoms of schizophrenia in patients with neuroborreliosis (Barnett 1991;Roelcke et al 1992;van den Bergen 1993;Grzywa et al 2004;B ä r et al 2005).…”
Section: Resultsmentioning
confidence: 95%
“…The most frequently debated and researched microbial agents are T. gondii (Torrey and Yolken 2003;Henriquez et al 2009) and herpes simplex virus type 1 (Shirts et al 2008; ( Barnett et al 1991). Roelcke et al (1992) described a meningopolyradiculitis patient with similar psychotic clinic to acute schizophrenia and second-stage neuroborreliosis caused by Borrelia burgdorferi . Another case study described a 64-year-old woman with Lyme psychosis, including hallucinations, found positive for Borrelia burgdorferi (van den Bergen et al 1993).…”
Section: Yolken Et Al 2011) In Addition It Is Reported Thatmentioning
confidence: 98%
“…There are reports of rapid decrease in LNB psychosis with ceftriaxone treatment (Roelcke et al 1992;Pfister et al 1993), though continuing symptoms requiring psychiatric treatment are not uncommon in LNB (Pfister et al 1991;Ljøstad and Mygland 2010;Markeljevic et al 2011). Similar to this case, one study in patients with post-treatment Lyme encephalopathy reported that ceftriaxone therapy resulted in cognitive improvement, with relapse after the antibiotic was discontinued (Fallon et al 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Only a few epidemiologic studies have evaluated the frequency of antibodies to Bb in psychiatric patients; one study found only 1/517 (0.2%) of all adult psychiatric patients had Lyme titer seropositivity (Nadelman et al, 1997) and the other larger study found that 322/926 (35%) of psychiatric inpatients had seropositivity to antibodies to Bb (Hajek et al, 2002). While a few cases have been reported (Hess et al, 1999; Mattingley and Koola, 2015; Roelcke et al, 1992) no studies to our knowledge have examined Lyme disease prevalence in patients with psychosis or schizophrenia or from a population of those being treated in the outpatient setting where infection may be more likely. It is interesting to note that seasonal (March to April) distribution of increased LD infection risk corresponds with the birth excess for schizophrenia in the winter months (Tochigi et al, 2004).…”
Section: Dear Editorsmentioning
confidence: 99%